“El desempeño laboral y carga de trabajo de los docentes de La Unidad Educativa La Maná, en época de pandemia covid 2019 - Álvarez García, Nataly Silvana (2021)
This research focuses on the work performance and workload of teachers in La Maná Educational Unit, covid 2019 pandemic time, self-assessment, and a survey was applied to twenty teachers of this section as instruments to get general data. Bibliographic research and field research was used. Theoretical, deductive, analytical, and empirical methods were also used, the assessment checked by experts also was applied to have more reliability when applying the instrument. In the same way, with the purpose of getting the significance of the two variable, descriptive and correlational research was applied. The study population consisted of twenty teachers from La Maná Educational Unit, daytime section, to whom the instruments before described were applied, the results revealed that due to the pandemic time , a good percentage of teachers have had a low work performance when carrying out their activities both academically as well as daily, teachers have been forced to take various personal training courses on the management of virtual programs, which has caused several physical and emotional health conditions, hurting their health. So with this research, some strategies were stated and so teachers can put them into practice to make the workload not so heavy and thus they can have a better work performance. In this sense, the current institutions must design and apply performance evaluation systems that allow them to effectively identify the flaws and limitations that are registered to correct them and guarantee the achievement of the institutional objectives. In this context, it must be considered in this regard that one of the main factors that affect work performance is the workload that teachers perceive in their work, together with the job stability offered by the institution, for this reason, the creation of a satisfactory environment for exercising and job stability, through the application of various strategies is necessary.